2021
DOI: 10.5144/0256-4947.2021.327
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients hospitalized with a diagnosis of COVID-19 pneumonia in a tertiary hospital in Turkey

Abstract: BACKGROUND: SARS-CoV2/COVID-19 emerged in China and caused a global pandemic in 2020. The mortality rate has been reported to be between 0% and 14.6% in all patients. In this study, we determined the clinical and laboratory parameters of COVID-19 related morbidity and mortality in our hospital. OBJECTIVES: Investigate the relationship between demographic, clinical, and laboratory parameters on COVID-19-related morbidity and mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Although the frequency of empirical antibiotic use may differ between studies, they are generally much lower compared to our results. This is compatible with the generally higher empiric antibiotic use in daily clinical practice in Turkey ( 3 , 13 , 14 ).…”
Section: Discussionsupporting
confidence: 75%
“…Although the frequency of empirical antibiotic use may differ between studies, they are generally much lower compared to our results. This is compatible with the generally higher empiric antibiotic use in daily clinical practice in Turkey ( 3 , 13 , 14 ).…”
Section: Discussionsupporting
confidence: 75%
“…Although male gender was significant in the univariate analysis of mortality, it lost its significance in the multivariate analysis. In studies evaluating inpatients with COVID-19 in Turkey, increasing age is observed to be one of the significant risk factors for mortality (Kokturk et al 2021 ; Medetalibeyoglu et al 2020 ; Birtay et al 2021 ). Research results from different countries are similar.…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, it has also been stated that patients with anosmia had higher regulated levels of lymphocytes and hemoglobin, and lower levels of d -dimer at admission [ 24 , 52 ]. The results also showed a higher hospitalization period, lymphocytes, hemoglobin, and glomerular filtration rate levels and lower d -dimer and C-reactive protein (CRP).…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed a higher hospitalization period, lymphocytes, hemoglobin, and glomerular filtration rate levels and lower d -dimer and C-reactive protein (CRP). Further changes in these parameters have been associated with a worse prognosis and an indirect measure of the systemic inflammatory response [ 15 , 41 46 , 52 ]. Some authors recommended monitoring these parameters in managing COVID-19 patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%